Tanggungjawab Negara Arab Saudi Dalam Pelanggaran Terhadap Hukum Diplomatik - Rutumalessy, Karina Alishe; Wattimena, Josina Augustina Yvonne; Waas, Richard Marsilio (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Countries in the world that live side by side must establish cooperative relations with one another. Relations between these countries require various rules so as to give birth to diplomatic and consular provisions, namely in the Vienna Convention on Diplomatic Relations and the Vienna Convention on Consular Relations. However, it is undeniable that even though it has been regulated in such a way, violations of the provisions of international law cannot be avoided because they are closely related to human relations. For example, the violations committed by Saudi Arabia.Purposes of the Research: This writing aims to find out the violations of Diplomatic Law committed and the form of accountability that must be fulfilled by Saudi ArabiaMethods of the Research: Using Normative Legal Research Type. This type of research will be carried out by examining and analyzing primary and secondary legal sources that are related to the problem being studied using a statute approach, a case approach, and a conceptual approach.Results of the Research: Based on this research, it can be concluded that Saudi Arabia has been proven to have violated diplomatic law by violating various principles that regulate the course of relations between countries and the provisions of the Vienna Convention on Diplomatic Relations and the Vienna Convention on Consular Relations. Thus, based on the provisions of the Responsibility of States for Internationally Wrongful Acts, Saudi Arabia can be held responsible for its mistakes in the form of giving restitution, compensation, or actions that cause satisfaction, for example, a formal apology